2018
DOI: 10.1029/2018je005572
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Noachian Paleoclimate of the Martian Highlands From Landscape Evolution Modeling

Abstract: The progressive degradation and loss of impact craters throughout the Noachian Period on Mars indicate prolonged erosion, rather than only a brief spike around the Noachian/Hesperian transition. The purpose of this study is to determine which suite(s) of geomorphic processes and rates best reproduce the relict Noachian landscape. We modeled the evolution of two study areas in the Martian highlands, Noachis Terra and Terra Cimmeria, to constrain the long-term erosional processes and rates that prevailed~4.0-3.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…However, while such a value might be plausible during the intense erosion in the Early Noachian (Hynek & Phillips, 2001), it is unreasonably high after this time, at least for most places on Mars. Estimates of post-Middle Noachian erosion rates are more than an order of magnitude lower (e.g., Golombek et al, 2006;Matsubara et al, 2018). For example,~2 m of denudation was inferred in Milna crater watershed in the Margaritifer Sinus Quadrangle during a similar period of time (Buhler et al, 2014).…”
Section: Overland Flowmentioning
confidence: 99%
“…However, while such a value might be plausible during the intense erosion in the Early Noachian (Hynek & Phillips, 2001), it is unreasonably high after this time, at least for most places on Mars. Estimates of post-Middle Noachian erosion rates are more than an order of magnitude lower (e.g., Golombek et al, 2006;Matsubara et al, 2018). For example,~2 m of denudation was inferred in Milna crater watershed in the Margaritifer Sinus Quadrangle during a similar period of time (Buhler et al, 2014).…”
Section: Overland Flowmentioning
confidence: 99%
“…In a hypo-fluvial regime earlier in the Noachian Period, deposition of impact ejecta exceeded fluvial and eolian denudation, leading to the net aggradation of the highland intercrater surfaces that Matsubara et al (2018) found when reproducing the topography of two study areas in a landscape evolution model (see also the Noachian craters with intact ejecta in Figures 5d, 7c, and 7d). These are transport-limited conditions in one sense, because the regolith could be transported if adequate runoff were available.…”
Section: Aqueous Weathering and Hypo-fluvial Erosionmentioning
confidence: 91%
“…This area is more densely dissected by valley networks, and here it is useful to observe how Late Noachian to Early Hesperian channelized flow responded to older intercrater topography. This study area is one of the sites reproduced in a simulation model by Matsubara et al (2018).…”
Section: Selection Of Study Areasmentioning
confidence: 99%
“…A brief summary of the MARSSIM model is presented in this section to provide context for our simulations and inferred results for the fluvial degradation of Endeavour. The reader is referred to papers by Barnhart et al (2009), Forsberg-Taylor et al (2004, Howard (1994Howard ( , 1997Howard ( , 2007, Howard et al (2005), and Matsubara et al (2011Matsubara et al ( , 2018 for detailed discussions of model development and past applications to the fluvial history of Mars.…”
Section: Marssim Landscape Evolution Modelmentioning
confidence: 99%
“…Fluvial period value adopted from Matsubara et al (2018) Postfluvial diffusion period values chosen after experimentation to produce lowered upper interior slopes, fill in interior channels, and maintain pediment surfaces…”
Section: Parameter Varied Explanationmentioning
confidence: 99%